Hawtrey, the Economic Problem - Homan, Paul T.; Hawtrey, R. G. (Quarterly Journal of Economics, 1928)
Hawtrey, The Economic Problem Get access Paul T. Homan Paul T. Homan Cornell University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 42, Issue 4, August 1928, Pages 678–684, https://doi.org/10.2307/1882539 Published: 01 August 1928